1992
DOI: 10.1136/hrt.67.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Management of myocardial infarction: implications for current policy derived from the Nottingham Heart Attack Register.

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Dubayova et al 34 reported from their systematic review that intensity of fear was associated with earlier help-seeking. Classic studies from Nottingham, United Kingdom, 35 and Rotterdam, the Netherlands 36 reported significantly longer delays in hospitalization and initiation of reperfusion therapies when patients sought advice from their primary care physician rather than calling an ambulance.…”
Section: Discussionmentioning
confidence: 97%
“…Dubayova et al 34 reported from their systematic review that intensity of fear was associated with earlier help-seeking. Classic studies from Nottingham, United Kingdom, 35 and Rotterdam, the Netherlands 36 reported significantly longer delays in hospitalization and initiation of reperfusion therapies when patients sought advice from their primary care physician rather than calling an ambulance.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have suggested that a patients decision to call physician increases the delay to hospital admission. 15,16 These, along with self treatment with rest or medication and an extended process of decision making in which the patient seeks the help of a physician or family member before obtaining hospital care contributes to prolong delay in seeking hospital care. We did not find any significant difference between early and late presenters regarding presence of co-morbidities, such as stroke, DM, hypertension and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that this approach increases prehospital delay in AMI [19, 20, 21, 22]. Improved patient and population education may help to increase direct access of AMI patients to the emergency medical system.…”
Section: Discussionmentioning
confidence: 99%